2020
DOI: 10.24106/kefdergi.3478
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Perceptions of Social Studies Prospective Teachers’ Sense of Efficacy

Abstract: Bu araştırmanın amacı, Sosyal Bilgiler öğretmen adaylarının mesleki özyeterliklerine ilişkin algılarını ortaya koymaktır. Bu amaç doğrultusunda, araştırmanın çalışma grubunu 12 üniversitede Eğitim Fakültelerinin 2014-2015 öğretim yılında İlköğretim Sosyal Bilgiler öğretmenliği 1.2.3.4. sınıflarında okuyan 2193 öğretmen adayı oluşturmaktadır. Araştırma tarama modelinde betimsel bir araştırmadır. Araştırmadan elde edilen sonuçlara göre, genel olarak Sosyal Bilgiler öğretmen adaylarının özyeterlik algıları incele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
1
5
0
5
Order By: Relevance
“…Within the framework of the first question of the research, classroom management competencies of teacher candidates were found to be at medium level. Similar findings were obtained in different studies on this subject (Bümen and Özaydın, 2013;Çapa, Çakıroğlu and Sarıkaya, 2005;Demirtaş, 2012;Kılıç and Saruhan, 2006;Kırmızı, 2011;Kinay, Elçiçek and Oral, 2015;Kuğuoğlu, 2005;Öksüz, Çevik, Baba and Güven, 2011;Recepoğlu and Ergün, 2017;Terzi and Tezci, 2007). It was concluded that the highest averages among classroom management competencies were in relationship management, physical organization management and time management, respectively, while the lowest averages were in behaviour management and teaching management competencies.…”
Section: Discussionsupporting
confidence: 85%
“…Within the framework of the first question of the research, classroom management competencies of teacher candidates were found to be at medium level. Similar findings were obtained in different studies on this subject (Bümen and Özaydın, 2013;Çapa, Çakıroğlu and Sarıkaya, 2005;Demirtaş, 2012;Kılıç and Saruhan, 2006;Kırmızı, 2011;Kinay, Elçiçek and Oral, 2015;Kuğuoğlu, 2005;Öksüz, Çevik, Baba and Güven, 2011;Recepoğlu and Ergün, 2017;Terzi and Tezci, 2007). It was concluded that the highest averages among classroom management competencies were in relationship management, physical organization management and time management, respectively, while the lowest averages were in behaviour management and teaching management competencies.…”
Section: Discussionsupporting
confidence: 85%
“…The Ohio Teacher Efficacy Scale, which is one of the frequently used teacher efficacy measurement tools, consists of three sub-dimensions: competence in instruction; competence in management; and competence in engagement (Tschannen-Moran & Woolfolk-Hoy, 2001) and was adapted to Turkish by various researchers (Baloğlu and Karadağ, 2008;Çapa, Çakıroğlu and Sarıkaya, 2005). In many studies conducted with these similar measurement tools, it was concluded that the self-efficacy of teachers and teacher candidates did not differ according to gender (Azar, 2010;Çakır, Kan & Sünbül, 2006;Erişen & Çeliköz, 2003;Jennett, Haris & Mesibov, 2003;Kahyaoğlu & Yangın, 2007;Recepoğlu & İbret, 2020;Telef, 2011). Considering the relationship between teacher self-efficacy and performance, it is seen that these studies support the research results.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…The review of literature shows that numerous studies have been done on class management in Turkey and classroom teachers have been investigated in those studies (Akın, 2006;Çelik, 2006;İlgar, 2007;Kayıkçı, 2009;Komitoğlu, 2009;Korkut & Babaoğlan, 2010;Yalçınkaya & Tonbul, 2002;Yaşar, 2008). However, it has been observed that there are very few studies on the classroom management of Social Studies teachers (Merey & Taşkın, 2018;Recepoğlu & Ergün, 2017;Sari, 2013). Similarly, when the relevant literature in Turkey is examined, since there are very few studies on the self-esteem of social studies teachers, it is expected that the present study will contribute to the relevant field of research.…”
Section: Introductionmentioning
confidence: 83%
“…The knowledge and the skills necessary to become a strong and modern society in terms of economic, social and cultural aspects can only be enabled through comprehensive and qualified education so that one can keep pace with today's rapidly developing world (Recepoğlu & Ergün, 2017). The greatest objectives of the countries are for the future generations to have the qualities that those countries aim for.…”
Section: Introductionmentioning
confidence: 99%